Sikap Ilmiah Siswa dalam Representasi Matematis Materi Aljabar Kelas VII SMP Negeri 13 Pontianak - Bistari, B; Salsabila, Kintan; Hamdani, H (Wacana Akademika: Majalah Ilmiah Kependidikan, 2024)
This study aims to implement the mathematical representation ability of students studied from scientific attitudes in students in class VII SMP Negeri 13 Pontianak, analysed based on the mathematical representation ability of symbols, algebraic material. The research method used was descriptive qualitative method. The subjects in this study were 30 students, namely class VII SMP Negeri 13 Pontianak. The results of the research on the attitude of curiosity of students 88% and the attitude of open-mindedness/cooperation 82% to 85%. The lack of scientific attitudes of students results in the ability to represent mathematical symbols, algebraic material is fairly weak. Individually there are 25 people categorised as weak, 2 people categorised as sufficient, and 3 people categorised as strong. While in groups there are 7 groups categorised as weak, and 5 groups categorised as sufficient. Students' mistakes in solving problems, namely those with algebraic nuances, also occur errors in writing the symbol of the operation, determining the positive or negative sign of an operation result, there is a lack of thoroughness, easily forgetting the material that has been delivered